Polarization imaging and classification of Jurkat T and Ramos B cells using a flow cytometer. Issue 9 (9th July 2014) - Feng, Yuanming; Zhang, Ning; Jacobs, Kenneth M.; Jiang, Wenhuan; Yang, Li V.; Li, Zhigang; Zhang, Jun; Lu, Jun Q.; Hu, Xin‐Hua
Abstract Label‐free and rapid classification of cells can have awide range of applications in biology. We report a robust method of polarization diffraction imaging flow cytometry (p‐DIFC) for achieving this goal. Coherently scattered light signals are acquired from single cells excited by a polarized laser beam in the form of two cross‐polarized diffraction images. Image texture and intensity parameters are extracted with a gray level co‐occurrence matrix (GLCM) algorithm to obtain an optimized set of feature parameters as the morphological "fingerprints" for automated cell classification. We selected the Jurkat T cells and Ramos B cells to test the p‐DIFC method's capacity for cell classification. After detailed statistical analysis, we found that the optimized feature vectors yield accuracies of classification between the Jurkat and Ramos ranging from 97.8% to 100% among different cell data sets. Confocal imaging and three‐dimensional reconstruction were applied to gain insights on the ability of p‐DIFC method for classifying the two cell lines of highly similar morphology. Based on these results we conclude that the p‐DIFC method has the capacity to discriminate cells of high similarity in their morphology with "fingerprints" features extracted from the diffraction images, which may be attributed to subtle but statistically significant differences in the nucleus‐to‐cell volume ratio in the case of Jurkat and Ramos cells. © 2014 International Society for Advancement of Cytometry